2010
DOI: 10.1111/j.1440-1819.2010.02087.x
|View full text |Cite
|
Sign up to set email alerts
|

A three‐year follow‐up study of the psychosocial predictors of delayed and unresolved post‐traumatic stress disorder in Taiwan Chi‐Chi earthquake survivors

Abstract: Aims:To predict the longitudinal course of posttraumatic stress disorder (PTSD) in survivors three years following a catastrophic earthquake using multivariate data presented six months after the earthquake.Methods: Trained assistants and psychiatrists used the Disaster-related Psychological Screening Test (DRPST) to interview earthquake survivors 16 years and older and to assess current and incidental psychopathology. A total of 1756 respondents were surveyed over the three-year follow-up period.Results: A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…Results of the current study corroborate a growing body of prior disaster mental health research, which found that post-disaster life stressors and traumas (Brewin et al, 2000; Cerda et al, 2012, in press; Kessler et al, 2012; Norris & Uhl, 1993; Norris et al, 2002a; Norris et al, 2002b; Tracy et al, 2011), including financial losses (Acierno et al, 2006; Galea et al, 2008; Rajkumar et al, 2011, in press; Su et al, 2010), are linked to severity, probable diagnoses, and chronicity of PTSD and related disorders. The finding that greater education was negatively related to a chronic symptom trajectory also accords with previous studies demonstrating the protective effect of this variable on risk for disaster-related PTSD and related mental disorders (Armenian et al, 2000; Norris et al, 2002a; Norris et al, 2002b; North et al, 2012; Yuan et al, 2012, in press).…”
Section: Discussionsupporting
confidence: 85%
“…Results of the current study corroborate a growing body of prior disaster mental health research, which found that post-disaster life stressors and traumas (Brewin et al, 2000; Cerda et al, 2012, in press; Kessler et al, 2012; Norris & Uhl, 1993; Norris et al, 2002a; Norris et al, 2002b; Tracy et al, 2011), including financial losses (Acierno et al, 2006; Galea et al, 2008; Rajkumar et al, 2011, in press; Su et al, 2010), are linked to severity, probable diagnoses, and chronicity of PTSD and related disorders. The finding that greater education was negatively related to a chronic symptom trajectory also accords with previous studies demonstrating the protective effect of this variable on risk for disaster-related PTSD and related mental disorders (Armenian et al, 2000; Norris et al, 2002a; Norris et al, 2002b; North et al, 2012; Yuan et al, 2012, in press).…”
Section: Discussionsupporting
confidence: 85%
“…However, younger age as one of the risk factors of PTSD has also been reported. [15,4649] In the present study, our results showed that age was not associated with the development of PTSD, which should be further verified in future.…”
Section: Discussionsupporting
confidence: 53%
“…In PTSD, the patients may develop memory impairments [47,48]. In this study, rats exposed to a PTSD model showed long-lasting effects (observed at least 1 month after exposure to the shock), suggesting impairments on spatial memory, since they spent more time in the opposite quadrant in the water maze task, while spending less time in the target quadrant.…”
Section: Discussionmentioning
confidence: 53%